Pairing fullerenes and porphyrins: Supramolecular wires that exhibit charge transfer activity - Wessendorf, Florian; Grimm, Bruno; Guldi, Dirk Michael; Hirsch, Andreas (Journal of the American Chemical Society, 2010)
A concept is elaborated of pairing electron donors and electron acceptors that share a common trait, wire-like features, as a powerful means to realize a new and versatile class of electron donor-acceptor nanohybrids. Important variables are fine-tuning (i) the complexation strength, (ii) the electron/energy transfer behavior, and (iii) the solubilities of the resulting architectures. In particular, a series of supramolecular porphyrin/fullerene hybrids assembled by the hydrogen bonding of Hamilton receptor/cyanuric acid motif has been realized. Putting the aforementioned variables into action, the association constants (K), as they were determined from H NMR and steady-state fluorescence assays, were successfully tweaked with values in the range of 10-10 M . In fact, our detailed studies corroborate that the latter reveal a dependence on the nature of the spacer, that is, p-phenylene-ethynylene, p-phenylene-vinylene, p-ethynylene, and fluorene, as well as on the length of the spacer. Complementary performed transient absorption studies confirm that electron transfer is indeed the modus operandi in our novel class of electron donor-acceptor nanohybrids, while energy transfer plays, if any, only a minor role. The accordingly formed electron transfer products, that is, one-electron oxidized porphyrins and one-electron reduced fullerenes, are long-lived with lifetimes that reach well into the time domain of tens of nanoseconds. Finally, we have used the distance dependence on electron transfer, charge separation and charge recombination, to determine for the first time a ß value (0.11) for hydrogen-bonding-mediated electron transfer. © 2010 American Chemical Society.